Factors Associated With Prolonged Psychological Distress Among Nurses and Physicians Engaged in COVID-19 Patient Care in Singapore and Japan - Morioka, Shinichiro; Tan, Ban Hock; Kikuchi, Hiroe; Asai, Yusuke; Suzuki, Tetsuya; Ashida, Shinobu; Kutsuna, Satoshi; Saito, Sho; Hayakawa, Kayoko; Tan, Thuan Tong; Kodama, Eiichi; Ohmagari, Norio (Frontiers in Psychiatry, 2022)
This study explores the factors contributing to the prolonged psychological distress of frontline nurses and physicians caring for COVID-19 patients in hospitals in Singapore and Japan. A cross-sectional survey between September and December 2020 yielded 1,644 responses (23.8%), from 62 nurses and 64 physicians in Singapore and 1,280 nurses and 238 physicians in Japan. Multivariate logistic regression analysis revealed that significant risk factors for prolonged psychological distress included being a frontline nurse, having an underlying medical condition, experiencing prejudice because they undertook COVID-19 patient care, having trouble dealing with panicked or uncooperative patients, and experiencing an outbreak of COVID-19 in the hospital. Factors inversely associated with psychological distress included age, number of beds in the hospital, clinical practice of carefully putting on and taking off personal protective equipment in daily COVID-19 patient care, and knowledge on COVID-19. These results could help us identify vulnerable healthcare providers who need urgent mental care during the COVID-19 pandemic. Measures that may reduce psychological strain include adequate supply of medical resources, education on precautionary measures, and communication strategies to combat discrimination against frontline healthcare providers.